The Effect of Type Cooperative Learning Model TGT on Deep Shooting Learning Outcomes Futsal Game for Students of Makassar Raya High School - Akbar Yusuf; Ikadarny Ikadarny; Andi Sahrul Jahrir (Universitas Majalengka, 2023)
Makassar Raya High School is one of the private schools in the city of Makassar where, when learning one of the basic techniques in futsal, namely the basic technique of sooting, the learning outcomes are still below average. So that at the time of shooting, there were still those who did not meet the desired target, so that student learning outcomes were unsatisfactory. The purpose of this study was to determine the effect of the TGT type of cooperative learning model on the shooting ability of SMA Makassar Raya Futsal. The population of this study used a total sampling technique with a total of 20 students. This type of research uses a one-group pretest-posttest design. At the beginning (pre-test) and end (post-test) of treatment. This type of research uses Based on inferential statistical analysis using the t-test yielded or obtained with a t-count value of 20.453 > ttable 1.725 (sig. value 0.000 <Î± 0.05), it means that there is a significant effect after being given push-up training. To prove the increase in shooting ability is evidenced by an average value of 2.03, or, in other words, the results of the t test obtained, the t-count is greater than the t-table at a significant level of Î± 0.05. So, it can be concluded that there is a significant influence of the TGT (X) cooperative learning model on the shooting ability (Y) of Makassar Raya High School students.